Sistem Informasi Rekam Medis Pasien Rawat Jalan Pada Puskesmas Pringkuku Kabupaten Pacitan - Puspitasari, Yuyun; Iriani, Siska (Speed - Indonesian Journal on Computer Science, 2014)
Description:Processing of medical records of patients in health centers Pacitan Pringkuku has not been computerized so that the data are missing and are found to double the data. It would require a information system patient medical record in health centers are computerized Pringkuku Pacitan to resolve the issue. The concept of information system design refers to the data processing activities of the medical records of patients in health centers. There are several stages in the development of information system design, namely the stage of system analysis, design, testing and implementation. The system is made ââwith a single user system and use the Netbeans Java program, Power Designer, and Windows XP as the operating system. The research method used in the design of information systems is the method of observation, interviews, and literature. While the purpose and benefits of this information system design that generate a computerized patient medical records. With this information system, the health center will be facilitated Pringkuku Pacitan in the processing of medical records of patients so as to minimize the errors if medical records are needed or wanted. Keywords: Information System Of Patient Medical Record Deskripsi:Proses pengolahan data rekam medis pasien di Puskesmas Pringkuku Kabupaten Pacitan selama ini belum terkomputerisasi sehingga data sering hilang dan sering ditemukan data yang ganda. Maka diperlukan sebuah sistem informasi rekam medis pasien di Puskesmas Pringkuku Kabupaten Pacitan yang terkomputerisasi untuk menyelesaikan premasalahanÂ  tersebut. Konsep perancangan sistem informasi ini mengacu pada kegiatan mengolah data-data rekam medis pasien yang terjadi di Puskesmas. Ada beberapa tahap dalam pengembanganÂ  perancangan sistem informasi ini, yaitu tahap analisis sistem, desain, pengujian dan implementasi. Sistem ini dibuat dengan sistem satu user dan menggunakan program Java Netbeans, Power Designer, dan Windows XP sebagai operasi sistemnya. Metode penelitianÂ  yang digunakan dalam perancangan sistem informasi ini adalah metode observasi, wawancara, dan kepustakaan. SedangkanÂ  tujuan dan manfaat dari perancangan sistem informasi ini yaitu menghasilkan sistem informasi rekam medis pasien yang terkomputerisasi. Dengan adanya sistem informasi ini, pihak Puskesmas Pringkuku Kabupaten Pacitan akan dimudahkan dalam proses pengolahan data rekam medis pasien sehingga dapat meminimalisir kesalahan jika data rekam medis tersebut dibutuhkan atau dicari. Kata kunci : Sistem Informasi Rekam Medis Pasien